The role of digital health in pandemic preparedness and response: securing global health? - Chisom Ogochukwu Ezenwaji; Esther Ugo Alum; Okechukwu Paul-Chima Ugwu (Global Health Action)
Background Digital health technologies, such as mobile applications, wearable devices, and electronic health record systems, have significantly enhanced global health security by enabling timely data collection and analysis, identifying infectious disease trends, and reducing infection risk through remote services. Objective This study assesses the role of digital health in pandemic preparedness and global health security response. It examines the application of digital health to early detection, surveillance, and data management in patient care. Methods We gathered data from scholarly articles published between 2019 and 2024 (found in PubMed, Science Direct, Google Scholar, and Web of Science), reports from the WHO, and case studies of recent pandemics. Topics discussed include digital health technologies, their use, benefits, and issues. We paid special attention to gathering the informed opinions and perspectives of specialists from various fields, including public health, technology, and government. The commentary synthesises these findings to offer suggestions for incorporating digital health into future pandemic preparedness and response. Results Digital tools improve communication, combat fake news, and reach the public, but data protection and public health remain challenges. Integration requires extensive research and collaboration between governments and the private sector. Conclusion The COVID-19 outbreak demonstrated the importance of digital technology in outbreak management, patient care, communication, and data sharing. As the world transitions into the post-pandemic phase, it will be important to build on these innovations and prepare for the challenges ahead in order to strengthen healthcare systems for future pandemics.